Exploring Future Scenarios of Antimicrobial Resistance: A Qualitative Study on Public Health Policy and Preparedness - Hojjati, Mahbobeh; Zadhasn, Zohreh (Journal of Foresight and Health Governance, 2024)
This study explores future scenarios of antimicrobial resistance (AMR). This qualitative research employed semi-structured interviews with 19 participants, including experts in public health, epidemiology, healthcare policy, and AMR research. Participants were recruited through online announcements and professional platforms. Theoretical saturation was used to determine the sample size. Data were collected through virtual interviews, transcribed verbatim, and analyzed using NVivo software. A grounded theory approach was applied, with open and axial coding used to identify key themes related to AMR governance, public health preparedness, technological developments, and societal factors. The study identified four major themes influencing AMR’s future trajectory: policy and governance challenges, public health preparedness gaps, technological and scientific barriers, and societal and behavioral factors. Policy inconsistencies, weak enforcement mechanisms, and inadequate surveillance systems were key governance issues. Public health preparedness remained insufficient, with limited healthcare capacity, delayed policy responses, and inadequate community engagement in AMR mitigation. Technological advancements, such as artificial intelligence and antimicrobial alternatives, were seen as promising but hindered by regulatory and financial constraints. Societal drivers of AMR included antibiotic misuse, pharmaceutical marketing influence, and public misconceptions. Participants emphasized the need for coordinated policy interventions, improved surveillance, and increased investment in research and innovation. Addressing AMR requires a globally coordinated response that integrates governance reforms, enhanced public health preparedness, technological advancements, and behavior change strategies. Strengthening regulatory frameworks, increasing funding for AMR initiatives, and promoting international collaboration are essential for mitigating future risks.